Starlikeness of Double Integral operators - Aghalary, Rasoul; Joshi, Santosh (Sarajevo Journal of Mathematics, 2024)
In this paper we investigate starlikeness of double integral operators by using second-order differential inequalities. We shall give some interesting conditions for $f(z)$ defined by double integral operators to be starlike of order $β$.